METHODOLOGY OF TEACHING ENGLISH - Tojiboyev Islom Odil o'g'li (Scholar Express Journal, 2021)
Teaching the basics of speech in English materials and types of speech activities are covered in detail and issues such as planning for teaching English in various educational institutions and methods of working on English tests. We hope that this guide will be used by teachers of secondary schools, academic lyceums and vocational colleges.
Keywords: Phometric; lexica; spelling; speech